Improved kiln saves trees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
A new kiln which produces lime more efficiently and to a standard required by Malawi's sugar industry - and reduces the amount of timber needed - is being used in the Chenkumbi Hills near Balaka, Malawi. The Zimbabwe office of the UK based ITDG...